2020
DOI: 10.1371/journal.pone.0229577
|View full text |Cite
|
Sign up to set email alerts
|

miR-101, miR-548b, miR-554, and miR-1202 are reliable prognosis predictors of the miRNAs associated with cancer immunity in primary central nervous system lymphoma

Abstract: MicroRNAs (miRNAs) inhibit protein function by silencing the translation of target mRNAs. However, in primary central nervous system lymphoma (PCNSL), the expression and functions of miRNAs are inadequately known. Here, we examined the expression of 847 miR-NAs in 40 PCNSL patients with a microarray and investigated for the miRNA predictors associated with cancer immunity-related genes such as T helper cell type 1/2 (Th-1/Th-2) and regulatory T cell (T-reg) status, and stimulatory and inhibitory checkpoint gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Besides, miR-30d, miR-93, and miR-181b are constituted of prognosis factors in PCNSL tumors 25 . While, miR-101, miR-548b, miR-554, and miR-1202 are associated with cancer immunity in PCNSL tumors 26 . Survivals of PCNSL patients are improved by HD-MTX, and PCNSL located in non-deep structures of brain respond better to HD-MTX alone than that located in deep-structures 27 .…”
Section: Discussionmentioning
confidence: 93%
“…Besides, miR-30d, miR-93, and miR-181b are constituted of prognosis factors in PCNSL tumors 25 . While, miR-101, miR-548b, miR-554, and miR-1202 are associated with cancer immunity in PCNSL tumors 26 . Survivals of PCNSL patients are improved by HD-MTX, and PCNSL located in non-deep structures of brain respond better to HD-MTX alone than that located in deep-structures 27 .…”
Section: Discussionmentioning
confidence: 93%
“…Inhibiting or down-regulating miR-548 promotes the tumor proliferation ( 96 ). One study proposed to serve miRNA-548 as a prognosis predictor in primary central nervous system lymphoma ( 97 ). Our study showed that miR-548 played an important role in the pathogenesis of autoimmune disease, which might be related to the TLR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The 2-year and 5-year survivals were evaluated. The process was repeated 10,000 times, and the average of AUC was calculated using the timeROC package in R, as described [ 43 ].…”
Section: Methodsmentioning
confidence: 99%